2001
DOI: 10.1111/j.1574-6968.2001.tb09461.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of lyso-galactolipids, C-2 and C-3O-acyl trigalactosylglycerol isomers, obtained from the lichenized fungusDictyonema glabratum

Abstract: A mixture of two lyso isomers of a galactolipid was obtained from Dictyonema glabratum. Aqueous hydrolysis gave rise to galactose and glycerol in a 3:1 molar ratio. ESI-MS spectroscopy gave, in the positive-ion mode, a pseudomolecular ion at m/z 839 and daughter ions with m/z 677, 600, 515 and 353, suggesting three galactosyl units linked to a glycerol moiety, substituted by one O-acyl group. 1D and 2D NMR experiments were used to characterize the glycolipid, and HMQC examination showed three anomeric signals,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…A small signal in the region of δ 174.5 (Fig. 4a) an ester carbonyl group [24]. FII fraction shows a more intense anomeric signal in the β configuration region of the spectrum (δ 103.7) than FI fraction (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…A small signal in the region of δ 174.5 (Fig. 4a) an ester carbonyl group [24]. FII fraction shows a more intense anomeric signal in the β configuration region of the spectrum (δ 103.7) than FI fraction (Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The EtOH extract of the sponge was partitioned between water and 1-butanol. The butanol extract was subjected to repeated chromatographic separations to give the new compound, araguspongine M ( 1 ), araguspongines B ( 2 ) and D ( 3 ) [ 7 , 8 ], dopamine ( 4 ), three galactosyl diacylglycerols ( 5–7 ) [ 9 13 ], 24-methyl cholesterol ( 8 ), 5, 6-dihydrocholesterol ( 9 ), β-sitosterol ( 10 ) [ 14 – 16 ], and three 5α,8α-epidioxy sterols ( 11 – 13 ) [ 17 , 18 ]. The structures of known compounds were determined on the basis of their spectral data and comparison with the previously reported values.…”
Section: Resultsmentioning
confidence: 99%
“…These compounds were also isolated from marine sponges, Phyllospongia foliascens [ 37 ] and Pseudoceratina sp. [ 38 ], and marine microorganisms, such as cyanobacteria [ 9 10 ], dinoflagellates [ 11 , 12 ], and a lichenized fungus [ 13 ]. HPLC analysis of the glycolipids fractions revealed that there were at least seven minor monogalactosyl and digalactosyl diacylglycerols, and several trigalactosyl diacylglycerols in this sponge.…”
Section: Resultsmentioning
confidence: 99%